Analiza telesne temperature predšolskih otrok med plavalnim tečajem - Mavsar, Tina (Šport (Ljubljana), 2020)
The purpose of the research was to establish what happens with the body temperature of preschool children during a swimming course. It was determined whether there are any differences in body temperature when teaching them by different methods of learning to swim with different procedures of teaching. Two methods of learning to swim were compared, the classical method where head-in immersion is included in the learning from the first hour onwards, and Fred%s method of learning to swim where the head-in immersion is not present at all.
Keywords: body temperature; classical method; Fred method; Fredova metoda; klasična metoda; plavanje; predšolski otroci; preschool children; sport; swimming; swimming course; šport; telesna temperatura; učenje plavanja